Senotherapeutics: An emerging approach to the treatment of viral infectious diseases in the elderly - Li, Zhiqiang; Tian, Mingfu; Wang, Guolei; Cui, Xianghua; Ma, Jun’e; Liu, Siyu; Shen, Bingzheng; Liu, Fang; Wu, Kailang; Xiao, Xuan; Zhu, Chengliang (Frontiers in Cellular and Infection Microbiology, 2023)
In the context of the global COVID-19 pandemic, the phenomenon that the elderly have higher morbidity and mortality is of great concern. Existing evidence suggests that senescence and viral infection interact with each other. Viral infection can lead to the aggravation of senescence through multiple pathways, while virus-induced senescence combined with existing senescence in the elderly aggravates the severity of viral infections and promotes excessive age-related inflammation and multiple organ damage or dysfunction, ultimately resulting in higher mortality. The underlying mechanisms may involve mitochondrial dysfunction, abnormal activation of the cGAS-STING pathway and NLRP3 inflammasome, the role of pre-activated macrophages and over-recruited immune cells, and accumulation of immune cells with trained immunity. Thus, senescence-targeted drugs were shown to have positive effects on the treatment of viral infectious diseases in the elderly, which has received great attention and extensive research. Therefore, this review focused on the relationship between senescence and viral infection, as well as the significance of senotherapeutics for the treatment of viral infectious diseases.